Self-Directed English Language Learning of EFL Students of Non-English Study Program in Indonesia - Trahkumala, Nilam; Hidayat, Nur (JELITA, 2025)
This study aimed to examine the learning strategies affecting success in the self-directed English language learning stage and the barriers faced by self-directed learners. The participants of this study were two university students from non-English majors who had learned English independently. They attained a high level of proficiency and multiple wins in English speech competitions, and active involvement in international seminars. The research design was narrative inquiry with two university learners from non English study program who have studied English autonomously, whether through software, digital sources, books, or other learning media and have reached a particular level of proficiency without participating in formal courses or language learning programs. The data were collected through semi-structured interview and the researchers conducted thematic analysis to analyzed it. The result indicated that the strategy of self-directed English learning typically begins with early exposure through video games and interactive computer use, supported by encouragement from family members. As learners transition into adulthood, audio-visual media and social networking platforms become increasingly effective tools for enhancing English proficiency. The integration of technology, combined with consistent learning efforts and adequate time investment, emerges as a crucial factor in optimizing self-directed language acquisition. Nevertheless, this study also identifies two primary challenges faced by learners: a misalignment between their personal interests and the formal curriculum, and persistent difficulties in applying grammatical knowledge during spoken communication.